Common biological processes and mutual crosstalk mechanisms between cardiovascular disease and cancer - Gao, Hanwei; Chen, Zhongyu; Yao, Yutong; He, Yuquan; Hu, Xin (Frontiers in Oncology, 2024)
Cancer and cardiovascular disease (CVD) are leading causes of mortality and thus represent major health challenges worldwide. Clinical data suggest that cancer patients have an increased likelihood of developing cardiovascular disease, while epidemiologic studies have shown that patients with cardiovascular disease are also more likely to develop cancer. These observations underscore the increasing importance of studies exploring the mechanisms underlying the interaction between the two diseases. We review their common physiological processes and potential pathophysiological links. We explore the effects of chronic inflammation, oxidative stress, and disorders of fatty acid metabolism in CVD and cancer, and also provide insights into how cancer and its treatments affect heart health, as well as present recent advances in reverse cardio-oncology using a new classification approach.